Ectoparasites associated with rodents (Rodentia) and marsupials (Didelphimorphia) from northeastern Argentina: new host and locality records - Benitez-Ibalo, Alicia Paola; Aguiar, Leonardo Dionel; Di Benedetto, Ingrid Maria Desireé; Mangold, Atilio Jose; Milano, Francisca; Debárbora, Valeria Natalia (Universidad Nacional Autónoma de México (UNAM), 2022)
Taxonomically, ectoparasites represent a very diverse group, which includes: fleas, lice, mites, and ticks, among others. The aim of this work is to extend the knowledge about the ectoparasite fauna associated with rodents and marsupials from Corrientes Province. For this purpose, 2 suburban sites in Corrientes City were sampled: Santa Ana de los Guácaras and San Patricio. Fifty-four mammal hosts were examined. Among the marsupials, 2 species were collected: Lutreolina crassicaudata Desmarest, 1804 and Didelphis albiventris Lund, 1840. The analyzed rodents included 3 species: Cavia aperea Erxleber, 1777, Oxymycterus rufus Fischer, 1814 and Oligoryzomys sp. Bangs, 1900. In total, 469 ectoparasites were collected including 5 genera of mites: Androlaelaps Berlese, 1903, Gigantolaelaps Nesbitt, 1951, Laelaps Koch, 1836, Mysolaelaps Fonseca, 1935, and Ornithonyssus Sambon, 1928; 3 species of ticks, Amblyomma ovale Koch, 1844, A. dubitatum Neumann, 1899, and Ixodes loricatus Neumann, 1899; 2 species of fleas: Polygenis axius Jordan & Rothschild, 1923 and Polygenis bohlsi Wagner, 1901, and 3 different lice, Trimenopon hispidum Burmeister, 1838, Gliricola sp. Schrank, 1781, and Gyropus sp. Nitzsch, 1818. These results provide host and locality records and new parasite-host associations.